A multiproxy reconstruction of the palaeoenvironment and palaeoclimate of the Late Pleistocene in northeastern Iberia: Cova dels Xaragalls, Vimbodí-Poblet, Paratge Natural de Poblet, Catalonia - López-García, Juan Manuel; Blain, Hugues-Alexandre; Bennàsar, Maria; Euba, Itxaso; Bañuls, Sandra; Bischoff, James; López-Ortega, Esther; Saladié, Palmira; Uzquiano, Paloma; Vallverdú, Josep (Boreas, 2012)
The Cova dels Xaragalls is a small open karst system, located in the municipality of Vimbodí-Poblet (Tarragona, Catalonia, NE Spain). It is an important Holocene archaeological site that was inspected in the 1970s but from which little has been published. New excavations starting in 2008 have exposed a deep Late Pleistocene stratigraphical sequence. In this paper, we present for the first time palaeoenvironmental and palaeoclimatic reconstructions of this Late Pleistocene succession on the basis of both the small-vertebrate assemblages and the charcoals. Results from the small-vertebrate associations along the sequence indicate that the landscape had open-woodland habitats in the vicinity of the Cova del Xaragalls, with wet points in the surrounding area. Woodland habitats were dominant throughout the sequence, as evidenced by the abundance of the species Apodemus sylvaticus, but were better developed during warm periods (layers C5 and C8), whereas during cold periods (layers C4 and C3) the environment was slightly more humid in response to higher mean annual precipitation and the opening of the landscape. The charcoal analysis indicates that the woodland surrounding the cave was composed mainly of Pinus (more than 90% was identified as Pinus), but that during the cold period (C3–C4) it incorporated some Quercus ilex/coccifera and Angiosperm indet., probably linked with greater precipitation. Comparisons are made with other long palaeoenvironmental sequences from the northeastern Iberian Peninsula and with global marine isotopic curves, providing a scenario for the palaeoclimatic and palaeoenvironmental changes that occurred during the Late Pleistocene in the woodland areas surrounding the Cova dels Xaragalls.
Keywords: CHARCOAL ANALYSIS; Cova dels Xaragalls; Late Pleistocene; Open woodlands (voyant); palaeoclimatic changes; palaeoenvironmental changes; small-vertebrate assemblages

Vegetation history, climate and human impact over the last 15,000 years at Lago dell’Accesa (Tuscany, Central Italy) - Drescher-Schneider, Ruth; de Beaulieu, Jacques-Louis; Magny, Michel; Walter-Simonnet, Anne-Véronique; Bossuet, Gilles; Millet, Laurent; Brugiapaglia, Elisabetta; Drescher, Anton (Vegetation History and Archaeobotany, 2007)
Interdisciplinary studies of the sediments of Lago dell’Accesa started in 2001. We present here results from the palynological study. The pollen diagram provides a record of vegetation and climatic change spanning over 15,000 years. The oldest pollen spectra show a late-glacial steppe vegetation typical of central and southern Italy during this period. The Late-glacial Interstadial, interrupted by two cooling events, is dominated by open deciduous oak forests. The Younger Dryas is represented by 150 cm of sediment and shows the presence of steppic vegetation. The Holocene vegetation is characterised by alternating dominance of deciduous oaks and Quercus ilex. The three zones characterised by Q. ilex are accompanied by peat layers marking lake-level lowering at ca. 8600–7900, 4600–4300 and 3700–2800 cal b.p. Between approximately 9000 and 6000 cal b.p. extensive Abies-forests existed on the Colline Metallifere located 15–20 km to the north and northeast of the lake. Local ﬁr populations may also have existed by the lake. Human impact starts at approximately 8000 cal b.p. during the Neolithic period, and increases at ca. 4300 cal b.p. Castanea and Juglans pollen is recorded from ca. 2800 cal b.p. The impact of the Etruscan settlement near the lakeshore is shown in the increasing values of arable crops, species of secondary forest canopy (Ericaceae, Pinus, Pistacia, Myrtus) and anthropogenic indicators (Chenopodiaceae, Plantago lanceolata, Rumex etc).
Keywords: Abies; Central Italy; Holocene; human impact; Late Pleistocene; Mediterranean vegetation; Pollen analysis

Late Pleistocene and Holocene pollen stratigraphy at Lago di Vico, central Italy - Magri, Donatella; Sadori, Laura (Vegetation history and archaeobotany, 1999)
A new pollen record from Lago di Vico (core V1) provides fundamental new information towards re- construction of flora and vegetation history in central Italy during the last 90 000 years. The chronological framework is secured by seventeen AMS 14C dates, one 4°Ar/39Ar date and tephra analyses. At the base of the pol- len record, i.e. shortly after the 4°Ar/39Ar date 87 000+ 7000 B.P., three phases with significant expansion of trees are recorded in close succession. These forest phases, which stratigraphically correspond to St Ger- main II (and Ognon?) and precede pleniglacial steppe vegetation, are designated by the local names Etruria I, Etruria II and Etruria III. During the pleniglacial, a number of fluctuations of angiosperm mesophilous trees suggest the presence of tree refugia in the area. The low- est pollen concentration values are recorded at ca. 22 000 B.P. which corresponds with other pollen records from the region. The late-glacial is characterized by an expansion in the arboreal pollen curves that is less pro- nounced, however, than in other pollen profiles from Italy. The Holocene part of the profile is consistently dominated by deciduous oak pollen. No major changes in arboreal pollen composition are recorded but several marked and sudden declines of the tree pollen concentra- tion suggest that the forest cover underwent dramatic changes. Clear evidence for human impact is recorded only when cultivated crops became important which dates to ca. 26304-95 B.P.
Keywords: Central Italy; Crater lake; Holocene; Late Pleistocene; Pollen analysis